Budaya Kerja dan K3 (Keselamatan dan Kesehatan Kerja) terhadap Kinerja Karyawan - Ghina Aryanti Barokah; Gendut Sukarno (Journal of Management and Bussines (JOMB), 2022)
This study aims to understand and examine the influence of Work Culture and K3 on the performance of PT Darmex Oil & Fats employees. This research method is descriptive quantitative. The population in the study were all production employees of PT Darmex Oil & Fats Bekasi Branch, with a total sample of 41 respondents. The analytical technique used in this study uses Partial Least Square. The results show that work culture has a positive effect on employee performance, as well as occupational safety and health (K3) has a positive effect on employee performance. In conclusion, work culture is able to contribute to the performance of employees of PT Darmex Oil & Fats Bekasi Branch. Also, K3 is able to contribute to the performance of employees of PT Darmex Oil & Fats Bekasi Branch. Keywords: Work Culture, Occupational Health and Safety, Employee Performance